Nanoalbumin-prodrug conjugates prepared via a thiolation‐and‐conjugation method improve cancer chemotherapy and immune checkpoint blockade therapy by promoting CD8+ T‐cell infiltration - Long Chen; Nuo Xu; Pan Wang; Haichuan Zhu; Zijian Zhang; Zhanqun Yang; Wenyuan Zhang; Hongyan Guo; Jian Lin (Wiley, 2023)
Abstract Protein-drug conjugates are emerging tools to combat cancers. Here, we adopted an indirect thiolation‐and‐conjugation method as a general strategy to prepare protein-drug conjugates. We found for the first time that this method led to the formation of nanometric conjugates, probably due to the formation of intermolecular disulfide bonds, which facilitated enhanced uptake by cancer cells. As a proof‐of‐concept application in cancer therapy, a nanometric albumin-doxorubicin prodrug conjugate (NanoAlb‐proDOX) was prepared. The nanometric size promoted its uptake by cancer cells, and the prodrug characteristic defined its selective cytotoxicity toward cancer cells in vitro and reduced side effects in vivo. In multiple tumor xenograft models, nanometric NanoAlb‐proDOX showed superior antitumor activity and synergy with immune checkpoint blockade, probably due to the synergistically enhanced tumor CD8+ T‐cell infiltration and activation. Hence, the thiolation‐and‐conjugation strategy may serve as a generally applicable method for preparing drug conjugates, and the proof‐of‐concept nanometric albumin-doxorubicin conjugate may be a good choice for antitumor therapy with the ability to co‐stimulate the efficacy of immune checkpoint blockade.